Recent Trends of Corporate Governance and Relevant Regulations of Capital Markets in India - Mohideen, A. K. (Prabandhan: Indian Journal of Management, 2012)
Capital market is one of the most important segments of the Indian financial system. It is the market available to the companies for meeting their requirements of the long-term funds. It refers to all the facilities and the institutional arrangements for borrowing and lending funds. In other words, it is concerned with the raising of money capital for purposes of making long-term investments. Corporate governance is about maximizing shareholder value legally, ethically and on a sustainable basis, while ensuring fairness to every stakeholder - the Company’s customers, employees, investors, vendor-partners, the government of the land and the community. It’s a reflection of a Company’s culture, policies, and its relationship with the stakeholders, and its commitment to values. Corporate governance also arises in response to the separation of ownership and controls the formation of joint-stock companies. The basic objective of setting up any regulations in the financial sector by a country is to safeguard the country’s financial system from risks, to protect the investor interests and promote competition. Even though some theories are there to explain the forms of regulation, more or less, but the basic objective of regulations has remained the same. This paper mainly focuses on the Corporate Governance system in India, recent trends and initiatives to promote corporate governance, the regulators of capital markets in India and the right policy initiatives of regulatory authorities.